Penggunaan Media Sosial Sebagai Alat Strategis Dalam Pendidikan Agama Islam - Shodikun Shodikun; Muhammad Hufron; Muhamad Rifa'i Subhi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of writing this work is to determine the use of social media as a strategic tool in Islamic religious education and its positive and negative impacts. This research is a literature review on the use of social media in Islamic religious education by relying on scientific literature and secondary sources such as education policies. Data was collected through keyword searches in academic databases and analyzed qualitatively to identify main findings regarding the impact of social media use in Islamic religious education. The results of this work are a) The use of social media in Islamic religious education requires a balance between maintaining ethical and moral values and exploiting its positive potential, such as spreading religious messages. The solution involves teacher innovation and collaboration with parents to monitor student behavior in interacting with social media. b) The use of social media in Islamic religious education has positive impacts, such as conveying religious messages and increasing students' technology skills, but raises challenges in the form of a lack of direct interaction between students and teachers as well as monitoring student understanding. The proposed solutions include systematic Islamic religious education and cooperation between teachers, parents and communities to ensure wise use of social media in promoting Islamic values.